The impact of culture and economic freedom for corruption based on selected European countries - Pluskota, Anna Maria (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The aim of this study is relationship between the selected index of corruption and measures of economic freedom of the state. I analyzed the size of the correlation between selected indicators of economic freedom and index of corruption. I also build panel econometric models. Statistical and econometric analysis showed that increasing economic freedom reduces corruptionin the analyzed group of countries. For Poland example has noticed a greater reduction in the scale of corruption arising from the growth of economic freedoms compared to other countries.